2008
DOI: 10.1002/tea.20268
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a doubt‐free teaching self: Self‐efficacy, teacher identity, and science instruction within diverse settings

Abstract: This study examined the influence of field placements settings with varying demographic profiles on preservice elementary teachers. Data were gathered at three points during the participants' final year in their teacher preparation program in order to chart changes over time in science teaching self‐efficacy beliefs. These measures were supplemented by interviews to investigate attitudes about teaching science in diverse settings. Gee's identity framework (2000) and the dimensions of teacher development descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(118 citation statements)
references
References 58 publications
2
106
0
4
Order By: Relevance
“…This science course was unusual by comparison with those reported by other authors (e.g., Avery & Meyer, 2012;Ford, Fifield, Madsen, & Qian, 2013;Liang & Richardson, 2009;Settlage et al, 2009) because it did not include opportunities for practising science teaching in field placements, and nor did it include the use of higher level inquiry as a pedagogy. Instead it used a relatively traditional approach in which science content was explained by the lecturer and explicit instructions were provided for the hands-on activities.…”
Section: The Science Content Coursementioning
confidence: 96%
See 1 more Smart Citation
“…This science course was unusual by comparison with those reported by other authors (e.g., Avery & Meyer, 2012;Ford, Fifield, Madsen, & Qian, 2013;Liang & Richardson, 2009;Settlage et al, 2009) because it did not include opportunities for practising science teaching in field placements, and nor did it include the use of higher level inquiry as a pedagogy. Instead it used a relatively traditional approach in which science content was explained by the lecturer and explicit instructions were provided for the hands-on activities.…”
Section: The Science Content Coursementioning
confidence: 96%
“…It has been found that science methods courses (i.e., those that teach how to teach science) and field placements that include opportunities to practice science teaching can often be successful in this regard (Settlage, Southerland, Smith, & Ceglie, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recent research into uncertainty and teacher education presents the idea that having some doubt and questioning one's self-efficacy may be an essential disposition of teaching (Schuck & Buchanan, 2012;Settlage, Southerland, Smith & Ceglie, 2009). However uncertainty can be seen as an unprofessional term (Munthe, 2001) because it implies that one is not prepared for the professional responsibilities of teaching.…”
Section: Implications For Teacher Educatorsmentioning
confidence: 99%
“…In this paper we will suggest that confidence or self-efficacy might not be the most appropriate success indicators of a teacher education program (see also Settlage, Southerland, Smith & Ceglie, 2009) and will make the provocative argument for the presence of doubt as a success indicator instead. We will indicate the value of awareness of complexity and ability to engage in self-analysis, as these are likely to lead to feelings of doubt and a healthy scepticism on graduation, due to realistic expectations of the task ahead.…”
Section: Introductionmentioning
confidence: 99%